To be assertive or not to be assertive: That is the question! Students' reactions to sexual harassment in academia - Cabras, Cristina; Sechi, Cristina; Agus, Mirian; Cois, Ester; Casula, Clementina; Raffo, Luigi; Mosca, Oriana (Frontiers in Psychology, 2022)
Introduction In the literature, no integrated definition of sexual harassment (SH) occurs but there is clear unanimity about SH being offensive, humiliating, and intimidating behavior. Within academic settings, SH has severe negative effects on students' physical or emotional wellbeing as well as on their ability to succeed academically. Methods The aim of this study was to investigate the relationship between sex, gender roles, and the ways to manage SH (assertive and nonassertive reactions) in university students. It was hypothesized that female students would report more nonassertive reactions compared to male students. In addition, following the Bem theory on gender roles and using the self-report tool by the same author, it is hypothesized that female and male students, who are classified as feminine, will report more nonassertive responses, whereas male and female students, who are classified as masculine, will report more assertive responses. Our hypothesis was tested with a sample of 1,415 university students (593 men, 41.9%, and 822 women, 58.1%) who completed a questionnaire approved by the local ethical review board for research from the end of January 2019 to the first half of February 2019. Results Contrary to our hypothesis, results showed that women react more than men in both assertive and nonassertive modalities. In addition, our results confirmed the main effect of both sex and gender roles on students' assertive and nonassertive reactions to SH in academia. Conclusion Educational programs about SH may prove useful in preventing its occurrence. Gender equality plans in academia can improve a nonsexist and safe environment for students. It is urgent to improve transparency and accountability of policies on the management of SH: academic institutions need to formulate a procedure to facilitate SH reporting, considering the sensitive balance of confidentiality and transparency issues. Support for the victims (social services, healthcare, legal representation, and advice concerning career/professional development) must be included.